Recurrent atherosclerotic cardiovascular disease events preventable with guideline recommended lipid-lowering treatment following myocardial infarction. (3rd October 2022) - Sakhuja, S; Bittner, V A; Brown, T M; Farkouh, M E; Levitan, E B; Rosenson, R; Safford, M M; Muntner, P; Chen, L; Sun, R; Noshad, S; Dhalwani, N; et al.
Abstract: Background: The 2018 American Heart Association/American College of Cardiology (AHA/ACC) cholesterol guideline provides recommendations for lipid-lowering therapy (LLT) including statins, ezetimibe and proprotein convertase subtilisin/kexin type 9 inhibitor (PCSK9i) to prevent recurrent atherosclerotic cardiovascular disease (ASCVD) events in adults with established ASCVD. Many adults with ASCVD who are recommended to take statins, ezetimibe and/or PCSK9i do not receive these medications. Purpose: To estimate the number of recurrent ASCVD events potentially prevented by population-wide use of guideline recommended LLT following a myocardial infarction (MI). Methods: We simulated the population-wide impact of receipt of 2018 AHA/ACC cholesterol guideline recommended LLT over 3 and 5 years among US adults with government health insurance through Medicare or commercial health insurance following hospital discharge for MI. We used data from patients with an MI hospitalization in 2018–2019 to estimate the percentage receiving guideline recommended LLT defined by having the medications available to take in the 30 days after their discharge date. We used data from patients with an MI hospitalization in 2013–2016 to estimate the 3 and 5-year cumulative incidence of recurrent ASCVD events (i.e., MI, coronary revascularization or ischemic stroke). The reduction in ASCVD events associated with guideline recommended LLT was estimated from a meta-analysis by the Cholesterol-Lowering Treatment Trialists Collaboration. We conducted a sensitivity analysis estimating the number and percentage of ASCVD events prevented if LLT recommendations from the 2019 European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) cholesterol guideline were followed. We repeated all analyses with recurrent coronary heart disease (i.e., MI or coronary revascularization) and ischemic stroke events as separate outcomes. Results: Among 279, 395 adults with an MI hospitalization in 2018–2019 (mean age 75 years, 54% men, mean low-density lipoprotein cholesterol 92 mg/dL), 27% were receiving guideline recommended LLT. With current lipid-lowering medication use, we estimated that 70, 698 (95% CI: 70, 311–71, 077) and 89, 255 (95% CI: 88, 841–89, 730) ASCVD events would occur in 3 and 5 years, respectively, after MI hospital discharge (Table, top panel). If all patients were to receive 2018 AHA/ACC guideline recommended LLT, the number of ASCVD events was estimated to be reduced by 21.6%, representing 15, 264 (95% CI: 14, 451–16, 679) events prevented over 3 years and 19, 271 (95% CI: 18, 245–21, 055) events prevented over 5 years. A higher number of recurrent ASCVD events were estimated to be averted following the LLT recommendations of the 2019 ESC/EAS cholesterol guideline (Table, bottom panel). Conclusions: Population-wide implementation of guideline recommended LLT in adults with an MI hospitalization could prevent a substantial number of recurrent ASCVD events. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen Inc.